Pemrograman Visual Basic Pendeteksi Dini Kecanduan Penggunaan Smartphone Terhadap Produktivitas Kerja Menggunakan Logika Fuzzy - Alvendo Wahyu Aranski; Sestri Novia Rizki (LPPM Universitas Putera Batam, 2018)
The development of smartphones today is very rapid. Emerging technologies, especially smartphones, have an impact on work productivity. In one day, people can access their smartphone about 15-50 times. This resulted in decreased employee productivity in a company. There are many negative things that happen if an employee uses his smartphone while working. The most important thing that will happen is the employee is less focused. If it is not focused, the job will be neglected and will not be finished. Thus resulting in a decrease in employee productivity itself. There are already many rules applied by a company, but this does not have a good impact on addiction to the use of this smart phone. With the help of fuzzy logic using the Mamdani method and applied into the app, it can detect early addictions for smartphone usage. The purpose of this study is very useful for the personnel of a company. The personnel department can quickly detect the prospective employees and can give a decision that the employee can be accepted or not into the company. With the existence of matlab calculations and applications, will facilitate the work of the personnel department in viewing the productivity of employees as early as possible. From the calculations that have been done, the results obtained that the use of smartphone addiction affect work productivity as much as 50,85 in accordance with the existing numbers on matlab calculations. This 50,85 figure shows enough part of his addiction to smartphone usage.